Adaptation mechanisms of Alcanivorax facilitating its predominance in marine environments - Zhen Chen; Shizheng Xiang; Yao Lu; Qiliang Lai; Chunming Dong; Jianyang Li; Guizhen Li; Zongze Shao (Frontiers in Marine Science, 2024)
Introduction Alcanivorax , a typical alkane-degrading bacterium, has demonstrated the ability to utilize inorganic electron donor in some reports. However, a comprehensive analysis of its potentiality to utilize inorganic electron donor is still lacking. Methods In this study, genomic and phylogenetic analyzes were used to explore the potential oxidative capacity of inorganic compounds in Alcanivorax . And its functions were verified through physiological experiments. Results The sulfur oxidation-related genes sqr and tsdA are prevalent and have various evolutionary origins. Potential genes for CO oxidation were present in 39 strains, whereas genes associated with iron, hydrogen, and ammonia oxidation were either rare or absent. The physiological functions of Sqr and TsdA were confirmed in six representative strains under heterotrophic conditions. Adding thiosulfate enhanced Alcanivorax growth. However, Alcanivorax bacteria perform sulfide detoxification through Sqr rather than by gaining energy via sulfide oxidation Although no strain was confirmed to be chemoautotrophs, we discovered that the two clades, A. xenomutans and A. profundimaris , can grow under conditions with very low organic matter. Discussion The ability to utilize inorganic compounds as a supplementary energy source and adapt to carbon oligotrophic growth may contribute to the prevalence of Alcanivorax in marine ecosystems.